Pengaruh Electronic Commerce Terhadap Keberhasilan Usaha Di Kawasan Tekstil Cigondewah Kota Bandung - Saputra, Aldy Rinaldi; Nuryanti, B. Lena; Utama, Rd. Dian Herdiana (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2018)
This research to find out the electronic commerce description of the success of the textile area business.This research was conducted in a span of less than one year, so the research design used was a cross sectional method. This study uses a verification approach with explanatory survey method. A total of 76 respondents as samples used saturated samples. The research questionnaire was used as a research instrument to collect data from respondents and the data analysis technique used was simple linear regression. The research findings is Electronic commerce has a significant effect on business success. The differences are found in independent variables, objects and research methods, population and research samples, research periods, measurement tools and research results, as well as theoretical sources and foreign journals and books.